Numerical simulation of micro-cracked interface - Ahmad Fauzy Bin Mohammed Gasi (Nanyang Technological University, 2023)
The presence of imperfections, such as microcracks, along the interface between two materials can significantly influence their mechanical behaviour. In this paper, we present a detailed review of the micromechanics of imperfect interfaces and their effects on material behaviour under tensile and shear loading. Finite element analysis is performed using ABAQUS on both micro and macro models to investigate the total strain energy and effective stiffness of the interface.